Implant-Prosthetic Rehabilitation in Bilateral Agenesis of Maxillary Lateral Incisors with a Mini Split Crest - M. M. Figliuzzi; A. Giudice; S. Pileggi; D. Pacifico; M. Marrelli; M. Tatullo; L. Fortunato (Case Reports in Dentistry)
The reported clinical case describes the surgical procedure of ridge augmentation by using a “split crest” technique with a partial thickness flap and a subsequent implant-prosthetic rehabilitation aimed at treating a bilateral agenesis of the upper lateral incisors. In such cases with vestibule-palatal and mesial-distal scarce bone thicknesses associated with the need of a proper functional and aesthetic rehabilitation, the split crest technique is particularly suitable. In the case we reported, because of the poor bone thicknesses, we performed a minimally invasive split crest which allowed a correct insertion of the fixtures. This technique allowed us to achieve an optimal functional and aesthetic rehabilitation; moreover, we obtained a good emergency profile, ensuring the vitality of the close teeth and ensuring a good primary stability and the following osseointegration of dental implants.